A new way for comparing solutions to non-technical electricity losses in South America - de Oliveira Ventura, Lucas; Melo, Joel D.; Padilha-Feltrin, Antonio [UNESP]; Fernández-Gutiérrez, Juan Pablo; Sánchez Zuleta, Carmen C.; Piedrahita Escobar, Carlos César (Elsevier, 2020)
Non-technical losses are a component of energy losses associated with energy theft and fraud by the final consumers, hindering revenues of distribution utilities. This paper aims to compare the implemented solutions in the countries of South America to reduce non-technical losses. In this comparison, we introduce a new indicator based on the World Bank's database as input information. Considering that some regulatory agencies take policy actions related to non-technical losses to improve the quality of the electricity supply, we also present a correlation analysis of the proposed indicator and the electricity supply quality index. This analysis shows that in most of South America's countries, there is a high correlation within the studied horizon. An adequate characterization of the temporal variation in the proposed indicator can characterize the evolution of the consumers' perception of the quality in the electricity supply. This indicator allows each country's regulatory agency to analyze how the performed action is reducing non-technical losses concerning neighboring countries.
Keywords: Energy theft; Non-technical losses; Power distribution system planning; Quality in the electricity supply